2018
DOI: 10.18632/oncotarget.23871
|View full text |Cite
|
Sign up to set email alerts
|

Association between PIK3CA alteration and prognosis of gastric cancer patients: a meta-analysis

Abstract: BackgroundIncreasing evidence suggests that dysregulation of phosphatidylinositol-4, 5-bisphosphate 3-kinase, catalytic subunit alpha (PIK3CA) plays an important role in carcinogenesis. However, the relationship between PIK3CA expression and gastric cancer (GC) prognosis remains controversial.MethodsWe searchedPubMed, Embase, Web of Science, and the Cochrane Library databases for relevant studies up to June 30, 2017. Primary outcomes were hazard ratio (HR), odds ratio (OR), and 95% confidence intervals (CI) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…The results showed that PIK3CA mutations were positively associated with T category, N category, stage, perineural invasion, and venous invasion. Consistent with other studies of GC (14,15,22,24,25), the current data also showed no association between PIK3CA mutation and prognosis. However, a novel finding in this study was that patients with exon 9 PIK3CA mutation exhibited lower DFS and OS rates than those without exon 9 PIK3CA mutation, although no independent correlation was demonstrated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that PIK3CA mutations were positively associated with T category, N category, stage, perineural invasion, and venous invasion. Consistent with other studies of GC (14,15,22,24,25), the current data also showed no association between PIK3CA mutation and prognosis. However, a novel finding in this study was that patients with exon 9 PIK3CA mutation exhibited lower DFS and OS rates than those without exon 9 PIK3CA mutation, although no independent correlation was demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…Another study also confirmed no relationship between PIK3CA mutations and clinical outcomes (13). However, in a recent meta-analysis of 2, 481 patients in 11 trials using pooled estimates for OS, Li et al evaluated the relationship between PIK3CA expression and GC prognosis and found no correlation between PIK3CA gene mutation and OS, yet significant association with poor tumor differentiation (14). In the case of EBV-GC, Böger et al reported that the PIK3CA status had no significant effect on OS or tumor-specific survival, suggesting an intratumoral heterogeneity of PIK3CA mutations (15).…”
mentioning
confidence: 96%
“…This has signi cance for the treatment of patients. A meta-analysis by Hua et al showed that PIK3CA mutations are indicators of poorly differentiated tumors [12]. These results are consistent with the immunohistochemical results.…”
Section: Discussionsupporting
confidence: 68%
“…Wu et al showed that PI3K/AKT/mTOR activation induced by PIK3CA upregulation promotes GC progression and chemoresistance [ 23 ]. A meta-analysis showed that high PIK3CA expression is closely related to poor prognosis in patients with gastric cancer [ 24 ]. Therefore, targeting PIK3CA is an effective strategy for increasing the survival time of patients with GC.…”
Section: Discussionmentioning
confidence: 99%